The Impact of U.S. Trade Tariff Announcements on Stock Market Dynamics: An Analysis of Volatility, Volume, and Abnormal Returns for LQ45 Export-Oriented Companies - Ana Meliyana; Nanu Hasanuh (Darul Yasin Al Sys, 2026)
The U.S. trade tariff policy announced in April 2025 triggered substantial turbulence in global financial markets, including the Indonesian capital market. This study aims to examine whether significant differences exist in stock price volatility, trading volume activity, and abnormal returns among export-oriented LQ45 stocks listed on the Indonesia Stock Exchange before and after the policy announcement. A quantitative approach using an event-study method was employed, with an observation window of 31 trading days from t−15 to t+15 and April 8, 2025, set as the event date. The sample consisted of 19 issuers selected through purposive sampling from the LQ45 index for the February–April 2025 period based on substantial export orientation. Data were analyzed using the Kolmogorov–Smirnov normality test to determine the appropriate difference tests, followed by the Wilcoxon Signed-Rank Test for stock price volatility and average abnormal return (AAR), and the Paired Sample t-Test for trading volume activity (TVA). The findings show that stock price volatility increased significantly by 31.9% after the announcement (p = 0.002), while TVA increased by 52.1% with the highest level of statistical significance (p = 0.000). In contrast, the difference in AAR before and after the announcement was not statistically significant (p = 0.570), reflecting the systemic nature of the shock, in which individual stock movements and market index movements occurred simultaneously. These findings support the relevance of semi-strong form market efficiency and Signaling Theory in emerging capital markets. This study concludes that trading volume and volatility provide stronger signals of market stress than abnormal returns during systemic policy shocks. The findings contribute to the event-study literature on emerging markets and offer practical implications for regulators and investors in monitoring market responses to external trade policy shocks.